Intellectualisation of African languages with particular reference to isiXhosa - Maseko, Pamela (Rhodes University, Faculty of Humanities, School of Languages, 2011)
The research explores the relationship between language and education, and motivates for the intellectualisation of African languages, isiXhosa in particular, and for their use in education. The main rationale behind this is that access to, and success in education can largely be realised if that education is mediated in one's first language. The thesis discusses works of prominent scholars who have written on the subject - relating cognitive abilities and achievement in education to language in which that education is offered. The lack of terminology in new domains in African languages as barrier to mother tongue education is laid bare by looking specifically at the history of intellectualisation of isiXhosa, from the missionaries in the 1820s up to the new endeavours as recently as 2008. Terminologies that were developed during the Bantu Education era, where development of isiXhosa and other indigenous African languages was accelerated in order to respond to the demands of moedertaal-onderwys (mother tongue education) are surveyed, and the process of their development analysed. Three main terminology lists developed during this period are analysed against terminology development principles, approaches and methods that are seen as a measure to ensure quality terminology development. The efforts of the development of isiXhosa during the post-apartheid South Africa, especially the government-driven initiatives, are also critiqued even though these are not as effective and as extensive, especially in education. The result of this analysis is that African languages and isiXhosa in particular, can be used in scientific disciplines and at the highest levels of education. Its grammar is advanced, and its lexicon is extensive such that new concepts that need to be named can be named, using appropriate term creation strategies. There are also technological tools such as WordSmith tools that can be used that can advance its development, ensuring that the concept represented in the newly-created term is precise, concise and appropriate in terms of its discipline. Therefore it is argued that, in the interim, terminologies should be developed, in various subjects, to support learning, which at this stage is mediated in English, for those students who have other languages as mother tongue. Those terminologies that have been developed in the various historical periods should be collated, revised and brought into the classrooms. The thesis argues that real intellectualisation of isiXhosa and other African languages rests on the use of these languages in classrooms and lecture halls, and in the value that all role players place on these languages.
Keywords: Xhosa language -- Study and teaching -- South Africa|Language and education -- South Africa|African languages